Evaluasi Model Otonomi Khusus Provinsi Papua dan Papua Barat - Sadu Wasistiono; Ika Sartika (Bestuurskunde: Journal of Governmental Studies, 2022)
The special autonomy fund expires in 2021, according to Law Number 21 of 2001 respecting Special Autonomy for the Province of Papua. As a result of this provision, political turmoil occurs. Law Number 2 of 2021 was immediately enacted by the government. There are still major issues that have not been resolved and will recur in the future, such as the lack of a complete and ongoing examination of the use of special autonomy funds. The goal of this research is to develop a unique autonomy evaluation model for Papua and West Papua Province. The CIPP Model (Context, Input, Process, Product) and the Gap Analysis Model were used in this study. The two models are used to assess education, health, infrastructure, and affirmation funding, which are the four key areas of focus for the utilization of special autonomy funds. The CIPP evaluation model can be used to comprehensively evaluate the use of special autonomy funds in two provinces in four areas, according to secondary data analysis and focus groups with stakeholders in the provinces of Papua and West Papua, as well as the cities of Jayapura and Sorong, including government officials, traditional leaders, youth leaders, women's leaders, and members of the Papuan People's Assembly (MRP). In the meanwhile, gap analysis can be used to map problems and solutions for the utilization of special autonomy funding in research sites.